A hybrid SEM-neural network method for identifying acceptance factors of the smart meters in Malaysia: Challenges perspective - Alkawsi G.A.; Ali N.; Mustafa A.S.; Baashar Y.; Alhussian H.; Alkahtani A.; Tiong S.K.; Ekanayake J. (Elsevier B.V., 2023)
Digital storage; Electric power systems; Energy efficiency; Internet of things; Smart meters; Analytic approach; Electrical power supply; Internet of thing (IOT); Literature reviews; Neural network method; Neural network model; Structural equation modelling (SEM); Unified theory of acceptance and use of technology; Neural networks